Pandan Wangi (Pandanus amaryllifolius Roxb.) Leaves Extract as Flies Repellent and Its Effect on Organoleptic Qualities of Chicken Meat (Faculty of Animal Science Universitas Brawijaya, 2020)
The research aims to determine the effectiveness of pandan wangi (Pandanus amaryllifolius Roxb.) leaves extract (PWLE) as flies repellent and understand its effect on the organoleptic qualities of chicken meat. The study was conducted in a completely randomized design with PWLE concentrations (0, 5, 10, 15, and 20%) as research treatments and replicated for four times. The flies repelling data were analyzed by using ANOVA and followed with Least Significance Different (LSD) test. Moreover, the organoleptic test results were analyzed by using Kruskal Wallis test. The results showed that the immersion of chicken meat in PWLE was effective to reduce the number of flies contamination with a repellent level of 0%; 8.25%; 36.5%; 53% and 59%, on the PWLE addition at 0, 5, 10, 15 and 20%, respectively. The results of the organoleptic test showed that the PWLE affected the preference of panelists on color, aroma, and texture parameters.